Woman in aviation, really? / Yong Azrina Ali Akbar ... [et al.] - Ali Akbar, Yong Azrina; Mohd Sabri, Syahirah Atikah; Yusrizan, Siti Liyana (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
There are plenty of women involved as flight attendants. However, how many women have handled behind the yoke? Most likely on the flight, ones can hear the captain's voice is male and most rarely it is female. How many women are there in the aviation office and airtraffic control where the area is dominated by men? Women in aviation industry seem as 'unable to fit in' for women's careers. This statement is supported by Miller and Budd (1999) which they found that the role of pilot was one of four occupations believed to be the most strongly sex stereotyped roles as cited in Miller and Hayward (2006). Aviation industry is seen as a masculine business that has been generalized for men.